2019
DOI: 10.1002/adsc.201900892
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme A‐Conjugated Cinnamic Acids – Enzymatic Synthesis of a CoA‐Ester Library and Application in Biocatalytic Cascades to Vanillin Derivatives

Abstract: We present a bioorthogonal method for the ligation of coenzyme A (CoA) with cinnamic acids. The reaction, which is the initial step in the biosynthesis of a multitude of bioactive secondary metabolites, is catalyzed by a promiscuous plant ligase and yields CoA conjugates with different functionalization in high purity and without formation of by‐products. Its applicability in biosynthetic cascades is shown for the direct transformation of cinnamic acids into natural benzaldehydes (like vanillin) or artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The active site volume of Nt 4CL2 was not only comparable with Hc AAE1 (relative volume 1.02/1) but also to the promiscuous A. thaliana 4CL2 ( At 4CL2; 1.03/1, Dippe et al ., 2019). Consequently, docking experiments of At 4CL2 showed that the promiscuity of the enzyme was defined by the amino acid composition rather than the size of the active site (Dippe et al ., 2019), ruling out a dominant role of the size exclusion mechanism for the recognition of the substrates. In the Hc AAE1 SBP, Phe‐397 appears to form a π–π stacking interaction with the phenyl ring of benzoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The active site volume of Nt 4CL2 was not only comparable with Hc AAE1 (relative volume 1.02/1) but also to the promiscuous A. thaliana 4CL2 ( At 4CL2; 1.03/1, Dippe et al ., 2019). Consequently, docking experiments of At 4CL2 showed that the promiscuity of the enzyme was defined by the amino acid composition rather than the size of the active site (Dippe et al ., 2019), ruling out a dominant role of the size exclusion mechanism for the recognition of the substrates. In the Hc AAE1 SBP, Phe‐397 appears to form a π–π stacking interaction with the phenyl ring of benzoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme variants were constructed by mutagenesis of pET28a(+)‐4HPA3H by the Quik Change II Site‐Directed Mutagenesis Kit (Agilent, Santa Clara, USA). The recombinant enzymes, which carried a hexahistidine tag at their N‐terminal, were produced in E. coli BL21(DE3) (see Supporting Information) and purified by immobilized Co 2+ ion affinity chromatography as described previously [39] . Purified proteins were checked for homogeneity by sodium dodecyl sulfate polyacrylamide gel electrophoresis, and their concentration was determined by the method of Bradford [40]…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant enzymes, which carried a hexahistidine tag at their N-terminal, were produced in E. coli BL21(DE3) (see Supporting Information) and purified by immobilized Co 2 + ion affinity chromatography as described previously. [39] Purified proteins were checked for homogeneity by sodium dodecyl sulfate polyacrylamide gel electrophoresis, and their concentration was determined by the method of Bradford. [40] Whole-cell bioconversions and product identification Reactions (10 mL) were performed in duplicates in auto-inducing medium [41] containing 200 μM hydroxylase substrate.…”
Section: Experimental Section Enzyme Production and Quantificationmentioning
confidence: 99%
“…The CoA-dependent pathway can be described as follows: feruloyl–CoA synthetase (FCS) ligates the acrylic group of phenylpropanoid acids and CoA to form acyl–CoA by adenosine triphosphate (ATP) driving. Then the enoyl–CoA hydratase (ECH) converts acyl–CoA into an aldehyde group . FCS is the rate-limiting enzyme throughout the progress of aromatic aldehyde synthesis. Our previous study elevated vanillin production by enhancing the expression level of FCS .…”
Section: Introductionmentioning
confidence: 97%
“…Simply regulating the expression level of FCS could not solve the low aromatic aldehydes production caused by rate-limited FCS. Hence, the poor catalytic ability of wild-type FCS to different natural phenylpropanoid acids has become a bottleneck for the efficient biosynthesis of aromatic aldehydes. , …”
Section: Introductionmentioning
confidence: 99%